The figure of Ki Hajar Dewantara and Its Relevance in the Challenges of 21st Century Education - Nur Annisa Islamiyah SR; Anita Chandra Dewi; Adela Adela; Nurul Magfirah; Julinda Yunita Sogen; Ahmad Rifki (International Journal of Global Sustainable Research, 2023)
In the history of Indonesian education, the name Ki Hajar Dewantara occupies an honorable position as the father of national education. The 21st century, known as the era of digitalization, brings a number of new challenges to the world of education. In the midst of the rapid flow of information, there are concerns about how education can shape students' strong character, integrity and responsibility Ki Hajar Dewantara's collection of works is a source of primary and secondary data. Secondary data sources consist of writings, other works, or previous research about Ki Hajar Dewantara. This research shows that one of the famous educational figures in Indonesia, Ki Hajar Dewantara, who is known as a pioneer of national education, is highly respected. Ki Hajar Dewantara's thoughts such as holistic thinking, education rooted in educational culture, and independence in education remain relevant and provide valuable guidance in the era of globalization and digitalization.